عبد الملك بن أبجر الكوفي واسهاماته العلمية - الجبوري نجلاء كريم مهدي (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
ʿAbd al-Malik ibn Abjar was one of the most prominent Christian physicians who excelled and mastered the medical profession. He resided in Alexandria, where he practiced and taught medicine during the rule of the Christian kings. When the Muslims conquered Egypt, Ibn Abjar abandoned Christianity and embraced Islam. His conversion to Islam is attributed to the Umayyad Caliph ʿUmar ibn ʿAbd al-ʿAzīz, who was a governor at the time. When ʿUmar ibn ʿAbd al-ʿAzīz assumed the caliphate, he took Ibn Abjar with him to the city of Antioch in the year 99 AH. From Antioch, Ibn Abjar moved to Harran and then to Kufa. Caliph ʿUmar relied on him for the practice and teaching of medicine, as he was among his close associates and favored figures. Ibn Abjar gained significant renown in Kufa, to the extent that he left behind descendants who practiced medicine and became well-known for it in the city.